Growing student teachers' reflective practice: explorations of an approach to video-stimulated reflection. Issue 5 (2nd September 2020) - Williams, Alexina Thorén
ABSTRACT: In Swedish teacher education, student teachers commonly work with assignments in small groups. To enable student teachers to grow, both personally and professionally, they need to reflect both individually and collectively with their teacher educators and fellow student teachers. However, research shows that there is a risk in teacher education to narrow reflection into a tool for teacher learning, and not recognizing it as an activity that challenges thought. To avoid this risk, the approach to video-stimulated reflection (VSR) explored in this study, considers not only the notion of reflection, but also the reflective process itself, and its potential for growing student teachers to create a reflective space collaboratively. Three groups of student teachers participated in the VSR on a field practice at a local science center. Two of the groups were preparing for teaching science in lower and upper primary school. The third group was preparing for teaching science in secondary school. A reflective cycle analysis was applied to detect reflection in the VSR interviews. The results demonstrate that the approach to VSR enabled a reflective process in all three groups. The affordances and constraints of the VSR and the role of the facilitator are discussed.